2013
DOI: 10.4028/www.scientific.net/amm.331.439
|View full text |Cite
|
Sign up to set email alerts
|

EMI Shielding Effectiveness of CNTs Composites

Abstract: A carbon nanotubes (CNTs) composite and its electromagnetic interference shielding effectiveness (SE) were investigated. Its absorptance, reflectance and shielding effectiveness (SE) were analysed. The CNTs composite has a shielding effectiveness (SE) of more than 25 dB (>99.68%) in frequency range from 30 MHz to 5 GHz. The testing results also demonstrate that the shielding mechanism of the CNTs composite is mainly EMI absorption of electromagnitic radiation. The high SE of the CNTs composite in the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Inspired by its good conductivity, the electromagnetic interference (EMI)-shielding performance and mechanism of CNTs composites have become the subject of much research. One such study reported 9 wt.% CNTs/ 91 wt.% acrylic resin composites containing a remarkable shielding effectiveness (SE) of more than 25 dB in frequency range from 30 MHz to 5 GHz [5], which is mainly a result of the absorption of electromagnetic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by its good conductivity, the electromagnetic interference (EMI)-shielding performance and mechanism of CNTs composites have become the subject of much research. One such study reported 9 wt.% CNTs/ 91 wt.% acrylic resin composites containing a remarkable shielding effectiveness (SE) of more than 25 dB in frequency range from 30 MHz to 5 GHz [5], which is mainly a result of the absorption of electromagnetic radiation.…”
Section: Introductionmentioning
confidence: 99%